PENGARUH PERSEPSI RISIKO, KEPERCAYAAN DAN KUALITAS INFORMASI TERHADAP PROSES KEPUTUSAN PEMBELIAN SECARA ONLINE (Studi pada Konsumen di Ungaran Kabupaten Semarang) - Adnan Surya Azhari, 13.05.51.0223; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2017)
The study of a very important purchasing decisions made by businessmen who market their products online. The purpose of the study was to analyze the influence of perception of risk, trust, information quality on purchasing decisions online. A sample of 100 respondents, using a non-probability sampling technique with the sampling method used is purposive sampling, its sampling with the criteria that the respondent is an adult and has been making purchases online. Methods of research data analysis using linear regression. The test results showed that there are negative and significant effect between the perception of risk on purchasing decisions online. there are significant positive and significant correlation between trust in purchasing decisions online, there is a positive and significant influence between information quality on purchase decisions online Â Keywords: risk perception,Â trust, information quality and purchasing decisions onlineDAFTAR PUSTAKAAkbar M.M. dan N. Parvez, (2009). Impact of Service Quality, Trust, and Customer Satisfaction on Customer Loyalty. ABAC Journal Vol. 29, No 1 (January-April 2009, pp.24-38).Alhasanah, Kerthadi, Riyadi. 2014. Pegaruh kegunaan, Kualitas Informasi dan Kualitas Interaksi Layanan Web E-commers terhadap Keputusan Pembelian Online (Survei Pada Konsumen www.Getscoop.com). Jurnal Administrasi Bisnis (JAB) Vol. 15 No. 2 Oktober 2014.Ardyanto, Denny; Susilo, Heru dan Riyadi, 2015. Pengaruh Kemudahan an Kepercayaan menggunakan E-Commerce terhadap Keputusan Pembelian Online (Survei Pada Konsumen www.petersaysdenim.com). Jurnal Administrasi Bisnis (JAB) Vol. 22 No. 1 Mei 2015.Basu Swastha. 2000. Pengantar Bisnis Modern, Pengantar Ekonomi Perusahaan Modern. Jakarta : Liberty.Chaffey, Dave; et al. 2007. Internet Marketing. Pearson Education limited., England.Djarwanto, PS dan Subagyo, Pangestu. 2000. Statistik Induktif. Edisi Ke-empat. Yogakarta: BPFE.Elissa, Ingge dan Mujiyana. 2013. Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Via Internet pada Toko Online. Jurnal Ekonomi Manajemen Universitas DiponegoroEngel, James F, et.al., 1995, Consumen Behavior, Alih Bahasa: Budiyanto, Jilid 1 dan 2, Bina Rupa Aksara, Jakarta.Fandy Tjiptono, 2008. Service Manajemen. Yogyakarta : Andi OffsetGefen, D., Karahanna, E., and Straub, D. W. 2004.